ORTHOPEDIC TREATMENT OF CLASS III MALOCCLUSION WITH MAXILLARY RETRUSION: A REVIEW - WAEL AHMED BAYOMY; ROZITA HASSAN; AUNG THU HTUN; SHAIFULIZAN ABDUL RAHMAN; NORMA BINTI AB. RAHMAN (International Journal of Pharma and Bio Sciences, 2016)
Class III malocclusion has been the subject of interest in many investigations, due to the treatment challenges. The standard care for correction of maxillary hypoplasia is to surgically advance the maxillary bone with a Le Fort I osteotomy after the adolescent growth completed. Orthodontic camouflage of class III malocclusion consists of extraction of teeth, proclinaton of maxillary incisors and retroclination of the mandibular incisors. However, orthopedic treatment of class III malocclusion can be done before puberty, although tooth – anchorage maxillary protraction using facemask is known as the regular orthopedic therapy there is other treatment modality that can be considered. The purpose of this paper is to update clinicians on the current orthopedic treatment options for class III malocclusion that is associated with maxillary retrusion